Practices and limits of advertising: A proposal of critical inquiry towards political campaigns - Montiel, Oscar (2020)
Interest in studying political advertising campaigns has grown in recent years, mainly in the United States (Daignault, Soroka, and Giasson, 2013). Likewise, approaching advertising from a critical angle has become very important (Hamilton, Bodle and Korin, 2017). The present makes a proposal to address what would be the tools and mechanisms of empathy and experience under which the advertising campaign of a presidential candidate in Mexico communicated with its target audience and what effects it caused in their groups of interest. The results show that it is a topic that is not widely addressed internationally and even more so in our country, and therefore proposes a methodology composed of various techniques and under a critical analysis, to be able to reflect on the invasion of privacy and lack of ethics that certain political campaigns have.